Altered gray matter structural covariance networks in drug-naïve and treated early HIV-infected individuals - Li, Ruili; Gao, Yuxun; Wang, Wei; Jiao, Zengxin; Rao, Bo; Liu, Guangxue; Li, Hongjun (Frontiers in Neurology, 2022)
Background: While regional brain structure and function alterations in HIV-infected individuals have been reported, knowledge about the topological organization in gray matter networks is limited. This research aims to investigate the effects of early HIV infection and combination antiretroviral therapy (cART) on gray matter structural covariance networks (SCNs) by employing graph theoretical analysis. Methods: Sixty-five adult HIV+ individuals (25-50 years old), including 34 with cART (HIV+/cART+) and 31 medication-naïve (HIV+/cART−), and 35 demographically matched healthy controls (HCs) underwent high-resolution T1-weighted images. A sliding window method was employed to create “age-bins”, and SCNs (based on cortical thickness) were constructed for each bin by calculating Pearson correlation coefficients. The group differences of network indices, including shortest path length of nodal (Nlp), betweenness centrality (Bc), number of modules, modularity, global efficiency, local efficiency, and small-worldness, were evaluated by ANOVA and post hoc tests employing the network-based statistics method. Results: Relative to HCs, less efficiency in terms of information transfer in the parietal and occipital lobe (decreased Bc) and a compensated increase in the frontal lobe (decreased Nlp) were exhibited in both HIV+/cART+ and HIV+/cART− individuals (P < 0.05, FDR-corrected). Compared with HIV+/cART− and HCs, less specialized function segregation (decreased modularity and small-worldness property), and stronger integration in the network (increased Eglob and little changed path length) were found in HIV+/cART+ group (P < 0.05, FDR-corrected). Conclusions: Early HIV+ individuals exhibited a decrease in the efficiency of information transmission in sensory regions and a compensatory increase in the frontal lobe. HIV+/cART+ showed a less specialized local segregation function, but a stronger global integration function in the network.